Advances of naturally derived biomedical polymers in tissue engineering - Hu, Tao; Fang, Jie; Shen, Yang; Li, Mingyang; Wang, Bin; Xu, Zushun; Hu, Weikang (Frontiers in Chemistry, 2024)
The extensive utilization of natural polymers in tissue engineering is attributed to their excellent biocompatibility, degradability, and resemblance to the natural extracellular matrix. These polymers have a wide range of applications such as delivering therapeutic medicine, detecting diseases, sensing biological substances, promoting tissue regeneration, and treating diseases. This is a brief review of current developments in the properties and uses of widely used biomedical polymers derived from nature. Additionally, it explores the correlation between the characteristics and functions of these materials in different biomedical applications and highlights the prospective direction for the advancement of natural polymer materials in tissue engineering.